A cidade de São Paulo, os trabalhadores e a natureza no final do século XIX e começo do XX - Fortti, Eduardo Luiz [UNIFESP] (2019)
This study tries to understand the social relations that were constructed from the connection of the poor workers of São Paulo’s city with the nature in the late nineteenth and early twentieth centuries. This relationship is loaded with numerous political and social interests.This intervention in the nature of São Paulo is loaded with numerous political and social interests.In the first part we seek to analyze the processes of urbanization and demographic growth that occurred in the city during the studied period and how nature was present throughout these processes. Then we seek to reconstruct how nature was present in the everyday life of the poor workers in the city, serving as a basis for food and occasional work. At last, we analyze how the public power perceived nature and intervened on it from the edition of laws and regulations, which directly affected the life of the poor workers of the city in their survival.